Digital Twins in Industry 5.0 – a systematic literatura review - Isaza Domínguez, Lauren Genith (European Public & Social Innovation Review, 2024)
Introduction: Industry 5.0 integrates advanced technologies with human-centric approaches to enhance manufacturing safety, human-robot collaboration, and efficiency. Digital twins, virtual replicas of physical systems, are central to this initiative to improve workplace safety and operational efficiency. Methodology: This SLR used a comprehensive search strategy across five digital libraries: IEEE Explore, Scopus, Taylor & Francis Online, ACM Digital Library, and Web of Science. Results: The findings highlight digital twins' contributions to worker safety through real-time monitoring, intelligent sensing, and proactive risk management. Human-robot collaboration is achieved through real-time data integration. Digital twins also improve manufacturing efficiency by enabling smarter, adaptive production systems. Discussion: Despite their potential, challenges such as data quality, computational complexity, cybersecurity, human factors, and socio-economic impacts need addressing. Conclusions: This SLR underscores the role of digital twins in advancing Industry 5.0, promoting safer, more efficient, and human-centric industrial environments.